Effect of Fremanezumab Monthly and Quarterly Doses on Efficacy Responses. Issue 7 (23rd May 2020) - Fiedler‐Kelly, Jill; Passarell, Julie; Ludwig, Elizabeth; Levi, Micha; Cohen‐Barak, Orit
Abstract : Objective: Exposure‐response (E‐R) models were developed to provide a description of the time‐course of treatment effect for monthly and quarterly dosing regimens of fremanezumab. Background: Fremanezumab is a monoclonal antibody for preventive treatment of episodic migraine (EM) and chronic migraine (CM). In phase 2b and 3 clinical studies of fremanezumab, significant reductions in migraine and headache days and other clinical endpoints were observed for patients with EM and patients with CM. Development of E‐R models relating individual‐specific measures of drug exposure to clinical endpoints provides a more granular understanding of the expected effects of different doses on therapeutic outcomes by accounting for variability in pharmacokinetic (PK) properties. Methods: Data from 2 phase 2b and 2 phase 3 studies of adults with EM or CM were used. Individual exposures were calculated from a population PK model and related to monthly migraine days in EM and moderate‐severe (M/S) headache days in CM. Model‐based stochastic simulations were performed to compare predicted responses for the various treatment regimens. Results: The effect of average fremanezumab concentration compared to placebo on the reduction in migraine days and M/S headache days was predicted by the models to be similar for 225 mg monthly and 675 mg once quarterly over time for both EM and CM patients. Both regimens were associated with better response than placebo. A similar percent of EM and CM responders was predicted across the range of observed body weights. Conclusions: Exposure‐response evaluations showed that both monthly (225 mg) and quarterly (675 mg) fremanezumab dosing regimens were appropriate in achieving clinical benefit in adult patients with EM or CM.